Daylight photodynamic therapy - Experience and safety in treatment of actinic keratoses of the face and scalp in low latitude and high brightness region - Luiz Eduardo Garcia Galvão; Heitor de Sá Gonçalves; Karine Paschoal Botelho; Juliana Chagas Caldas (Sociedade Brasileira de Dermatologia, 2017)
ABSTRACT Daylight photodynamic therapy has been used in countries with high latitudes during the summer for actinic keratoses treatment with reports of similar efficacy to conventional photodynamic therapy. We evaluate its safety in 20 patients in the city of Fortaleza, a local with low latitude and high brightness. Sixteen patients did not report any discomfort due to the procedure. Daylight photodynamic therapy is an easy application method with great tolerability by the patient and has the possibility of being performed throughout the year in these regions. It can mean a promising tool in the control of skin cancer.